Gender differences in awareness and adoption of climate-smart agriculture practices in Bangladesh - Bryan, Elizabeth; Kato, Edward; Bernier, Quinn (CAB International, 2021)
This paper analyzes gender differences in awareness and adoption of climate-smart agriculture (CSA) practices using data from a survey administered to men and women within the same households in southwestern Bangladesh. Access to sources of agricultural and climate information is low for both men and women, and women have particularly low access to key information sources. As a result of limited access to information sources and different roles in agriculture, women also tend to be less aware of practices for CSA. Gender gaps in adoption are smaller among those who are aware of CSA practices. Moreover, women are more likely than men to adopt some practices, particularly those related to their gendered roles, such as improved livestock feeding practices and grain storage when they are aware of the practices. Other factors, besides lack of awareness, also emerge as important determinants of adoption, including household wealth, as measured by size of landholdings, labor availability, access to credit, experience with climate shocks, and perceptions of future climate risk. The results suggest that greater efforts to reach both men and women with information on CSA would increase awareness and adoption of climate-smart practices.